A Look Back: A Commentary. (December 2020) - Puglisi, Gemma
An assistant professor and native Washingtonian looks back at the l970s and the impact of Watergate, Nixon, women in journalism and academia, and how some things have changed and how some things remain the same. The essay also examines what the AEJMC Journal was talking about during this period and what was on the minds of educators.